Comparison of widefield swept-source optical coherence tomography angiography with ultra-widefield colour fundus photography and fluorescein angiography for detection of lesions in diabetic retinopathy. Issue 4 (26th June 2020) - Cui, Ying; Zhu, Ying; Wang, Jay C; Lu, Yifan; Zeng, Rebecca; Katz, Raviv; Vingopoulos, Filippos; Le, Rongrong; Laíns, Inês; Wu, David M; Eliott, Dean; Vavvas, Demetrios G; et al.
Abstract : Aims: To compare widefield swept-source optical coherence tomography angiography (WF SS-OCTA) with ultra-widefield colour fundus photography (UWF CFP) and fluorescein angiography (UWF FA) for detecting diabetic retinopathy (DR) lesions. Methods: This prospective, observational study was conducted at Massachusetts Eye and Ear from December 2018 to October 2019. Proliferative DR, non-proliferative DR and diabetic patients with no DR were included. All patients were imaged with a WF SS-OCTA using a Montage 15×15 mm scan. UWF CFP and UWF FA were taken by a 200°, single capture retinal imaging system. Images were independently evaluated for the presence or absence of DR lesions including microaneurysms (MAs), intraretinal microvascular abnormalities (IRMAs), neovascularisation elsewhere (NVE), neovascularisation of the optic disc (NVD) and non-perfusion areas (NPAs). All statistical analyses were performed using SPSS V.25.0. Results: One hundred and fifty-two eyes of 101 participants were included in the study. When compared with UWF CFP, WF SS-OCTA was found to be superior in detecting IRMAs (p<0.001) and NVE/NVD (p=0.007). The detection rates of MAs, IRMAs, NVE/NVD and NPAs in WF SS-OCTA were comparable with UWF FA images (p>0.05). Furthermore, when we compared WF SS-OCTA plus UWF CFP with UWF FA, the detection rates of MAs, IRMAs, NVE/NVD and NPAs were identical (p>0.005). Agreement (κ=0.916) between OCTA and FA in classifying DR was excellent. Conclusion: WF SS-OCTA is useful for identification of DR lesions. WF SS-OCTA plus UWF CFP may offer a less invasive alternative to FA for DR diagnosis.